2022
DOI: 10.1002/est2.344
|View full text |Cite
|
Sign up to set email alerts
|

Development of nano‐enhanced phase change materials using manganese dioxide nanoparticles obtained through green synthesis

Abstract: The current paper summarizes the development of nano‐enhanced phase change materials (NPCMs) using capric acid (CA) and manganese dioxide (α‐MnO2) nanoparticles. The nanoparticles were obtained by the green synthesis technique using the leaves of Ficus retusa plant. The obtained nanoparticles were used in 1%, 2%, and 3% weight fractions in the nano‐formulations. The field‐emission scanning electron microscopy (FESEM) was employed to confirm the morphological structure and energy‐dispersive X‐ray (EDX) spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…As noted in prior research studies, interactions between the nanoparticles and the PCM at the nanoscale influence thermodynamic properties, including intermolecular forces, resulting in alterations in the energy needed for phase transition [48,49].…”
Section: Thermal Stability and Heat Transitionsmentioning
confidence: 81%
“…As noted in prior research studies, interactions between the nanoparticles and the PCM at the nanoscale influence thermodynamic properties, including intermolecular forces, resulting in alterations in the energy needed for phase transition [48,49].…”
Section: Thermal Stability and Heat Transitionsmentioning
confidence: 81%
“…This critical survey provides information on energy harvesting and conversion using PCMs enhanced with nanostructures. Anand et al [12] prepared a capric acid nano-enhanced (NE) PCM using manganese dioxide nanoparticles at different concentrations and reported that the LH was in the 145-164 kJkg −1 range. Metallic nanoparticle nano-inclusions are beneficial since they have less of an impact on the PCM's ability to store energy.…”
Section: Introductionmentioning
confidence: 99%
“…Green synthesis, a simpler alternative to traditional methods, aims to reduce harsh processing conditions. This approach involves the use of bacteria, fungi, and human cells as viable systems for green synthesis 1‐6 . Metal oxides are highly significant nanomaterials with versatile applications in various fields such as environment, health, and industry.…”
Section: Introductionmentioning
confidence: 99%
“…This approach involves the use of bacteria, fungi, and human cells as viable systems for green synthesis. [1][2][3][4][5][6] Metal oxides are highly significant nanomaterials with versatile applications in various fields such as environment, health, and industry. Cadmium oxide, in particular, has been extensively studied and utilized.…”
Section: Introductionmentioning
confidence: 99%